To Be Experienced or Not? Unpacking the Relationship between Leader Tenure and Counterinsurgency Efforts - Duveroglu, Buse (Terrorism and political violence, 2025)
Although countering insurgencies through violence is common yet costly, we occasionally observe governments take this cost by adopting non-violent strategies. Hence, under what circumstances do leaders choose non-violent or violent ones in tackling with insurgencies? We empirically investigate how leader experience in office affects what type of counterinsurgency measures leaders employ, and how domestic political constraints condition the decision-making process. We argue that inexperienced leaders tend to use violence, while experienced ones may adopt conciliatory tactics, as the former are more risk prone to prove their strong leadership immediately. However, we also contend that institutional mechanisms could moderate this effect depending on the level of constraints they impose. Drawing on Asal et al. dataset on governments’ counterinsurgency activities, we find that inexperienced leaders are more likely to resort to violence as a counterinsurgency strategy; whereas experienced ones are more likely to avoid solely violent measures, and adopt non-violent ones, as well. Plus, the effect is conditional on regime type, as experienced leaders’ acts vary depending on if they maintain a sear in a democratic or anocratic regime. Our findings contribute to the conflict studies by opening the door to the examination of leader-level factors on counterinsurgency more explicitly.